The Effectiveness of Using Vehicle Electric and Electronic Self-learning Module towards the Understanding of Automotive Students At Vocational College: Preliminary Study - A/P G. Ganesen, Milashini; Khair Noordin, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The automotive sector is a fast-growing sector in our country. Self-learning modules are defined as learning materials that allow students to work independently with minimum teacher guidance to achieve solid knowledge and skills. The study reported that vocational college automotive technology students do not have a standardized curriculum for automotive learning; instead, they still use the worksheet as reference material. The research thus aims to define the level of difficulty of topics, the level of student understanding in electrical and electronic subjects, and the importance of using a self-assessment module. 48 students of Diploma in Automotive Technology (DAT) were chosen using purposive sampling techniques from three vocational colleges. Analysis of data was done using the SPSS-Windows software version 24. The results of descriptive analyses for the difficulty level of topics in vehicle electric and electronic subjects show that the automotive students are weak in the topics of charger systems, starting systems, and wiring systems. Meanwhile, the outcome of formative test results showed that the majority of students received low scores, which are in the fail category. The importance of using a self-learning module result showed that students strongly agreed to use the self-learning module. Thus, during the process of teaching and learning, the user is expected to have effective alternative learning material.